Systematic cross section measurements of (α,γ) reactions for astrophysics - Provatas, G.; Foteinou, V.; Axiotis, M.; Lagoyannis, A.; Demetriou, P.; Harissopulos, S.; Becker, H.-W.; Rogalla, D.; Netterdon, L.; Winkens, J.; Zilges, A. (HNPS Advances in Nuclear Physics, 2019)
N/A